Azatruxene‐Based, Dumbbell‐Shaped, Donor–π‐Bridge–Donor Hole‐Transporting Materials for Perovskite Solar Cells. Issue 48 (30th July 2020) - Illicachi, Luis A.; Urieta‐Mora, Javier; Calbo, Joaquín; Aragó, Juan; Igci, Cansu; García‐Benito, Inés; Momblona, Cristina; Insuasty, Braulio; Ortiz, Alejandro; Roldán‐Carmona, Cristina; Molina‐Ontoria, Agustín; Ortí, Enrique; et al.
Abstract: Three novel donor–π‐bridge–donor (D ‐π‐D) hole‐transporting materials (HTMs) featuring triazatruxene electron‐donating units bridged by different 3, 4‐ethylenedioxythiophene (EDOT) π‐conjugated linkers have been synthesized, characterized, and implemented in mesoporous perovskite solar cells (PSCs). The optoelectronic properties of the new dumbbell‐shaped derivatives (DTTXs) are highly influenced by the chemical structure of the EDOT‐based linker. Red‐shifted absorption and emission and a stronger donor ability were observed in passing from DTTX‐1 to DTTX‐2 due to the extended π‐conjugation. DTTX‐3 featured an intramolecular charge transfer between the external triazatruxene units and the azomethine–EDOT central scaffold, resulting in a more pronounced redshift. The three new derivatives have been tested in combination with the state‐of‐the‐art triple‐cation perovskite [(FAPbI3 )0.87 (MAPbBr3 )0.13 ]0.92 [CsPbI3 ]0.08 in standard mesoporous PSCs. Remarkable power conversion efficiencies of 17.48 % and 18.30 % were measured for DTTX‐1 and DTTX‐2, respectively, close to that measured for the benchmarking HTM spiro‐OMeTAD (18.92 %), under 100 mA cm −2 AM 1.5G solar illumination. PSCs with DTTX‐3 reached a PCE value of 12.68 %, which is attributed to the poorer film formation in comparison to DTTX‐1 and DTTX‐2 . These PCE values are in perfect agreement with the conductivity and hole mobility values determined for the new compounds and spiro‐OMeTAD. Steady‐state photoluminescence further confirmed the potential of DTTX‐1 and DTTX‐2 for hole‐transport applications as an alternative to spiro‐OMeTAD. Abstract : Hole‐transporting materials : Donor–π‐bridge–donor triads based on triazatruxene units, covalently linked through different π‐conjugated spacers in a dumbbell‐shape fashion, have been synthetized and tested in perovskite solar cells as hole‐transporting materials. Power conversion efficiencies up to 18.3 % in conventional mesoporous perovskite solar cells have been achieved, showing a strong dependence on the surface morphology of the new hole‐transporting materials.